Safety of the concomitant cholecystectomy during laparoscopic sleeve gastrectomy in patients with symptomatic gallstone: A single-center experience - Lale, Azmi; Yur, Mesut; Doğan, Oğuz; Kırkıl, Cüneyt; Aygen, Erhan (My University, 2021)
Introduction: There are still controversies in the management of gallstones in patients who are candidate for bariatric surgery. The aim of this study was to evaluate the effect of the concomitant cholecystectomy (CC) during laparoscopic sleeve gastrectomy (LSG) on post-operative short-term complications in patients with symptomatic gallstone. Materials and Methods: After exclusion and inclusion criteria, a total of 251 patients were included in the study. Patients were divided into two study groups as Group A (only LSG, n=214) and Group B (LSG + CC, n=37). Results: Female-to-male ratio was 2/1 in Group A and 8/1 in Group B (p=0.01). The mean age, comorbid disease distributions, length of stay, and initial body mass index were similar in both groups. The differences in the rates of postoperative 30-day minor and major complications in Group A (7.5% and 2.8%, respectively) and Group B (18.9% and 2.7%, respectively) were not significant (p=0.64). CC prolonged the operation time at an average of 15 min (p<0.001). Conclusion: CC during LSG is a safe procedure in patients with symptomatic gallstone, which has an acceptable increase in operation time and does not cause an increase in minor or major complications and prolongation on length of stay
Keywords: Gastroenteroloji ve Hepatoloji; Cerrahi